Globalisation and Women’s Work in the Beedi Industry - Pande, Rekha (Studia Historiae Oeconomicae, 2019)
The present paper views globalisation and women’s work and exploitation in a micro enterprise in India, the beedi (indigenous cigarette) industry with a case study from one of the states in India. Rural occupational structures and employment patterns in India have undergone a transition in the last few decades due to globalisation. Newer forms of employment like construction work, domestic services and beedi making have become alternatives to agricultural labour for women. Beedi is an indigenous cigarette, in which tobacco is rolled in a tendu leaf and tied with a cotton thread. This is smaller and less expensive than a cigarette and in the popular imagination it stands for the working class. This work is done sitting at home and mostly women and girls do it. This is a very gendered industry, for only women and girls that too from low-income groups make beedis. There is a lot of exploitation in this industry and this has only increased with the advent of globalisation but this is generally ignored by data gathering systems, policy makers and administrators. There is an occupational health hazard too for many of these workers suffer from various health hazards not because they are smoking these beedis but because they are making them.